Intravenous lidocaine infusion during laparoscopic cholecystectomy: efficacy and safety in pain management - Kuchyn, Yu. L.; Babich, V. P.; Bielka, K. Yu.; Martischenko, K. D. (Pain medicine, 2017)
Systemic administration of lidocaine can improve perioperative analgesia for patients during laparoscopic cholecystectomy and reduce opiate-associated side effects. Aim of the study was to determine the efficacy and safety of intravenous infusion of lidocaine for pain relief during laparoscopic cholecystectomy. A prospective controlled study was conducted at the Department of Surgery, Anesthesiology and Intensive Care in the Institute Of Postgraduate Education of Bogomolets National Medical University. The study enrolled 60 adult patients with acute and chronic cholecystitis, who were elected for laparoscopic cholecystectomy. Patients were randomised to 2 groups – Group L (lidocaine) and Group C (control). Intraoperative intravenous infusion of lidocaine during laparoscopic cholecystectomy reduced average pain intensity at rest and during movement, the number of patients with moderate and severe pain, the amount of analgesia “on demand”. The use of intraoperative lidocaine infusion allowed to significantly reduce the consumption of intraoperative anesthetics and analgesics as well as in early postoperative period, and accordingly reduce the incidence of opiate-associated adverse events, accelerate the recovery of bowel function after laparoscopic cholecystectomy and reduce the incidence of intraoperative hypertension.